Evaluación de la oferta de Servicios Turísticos del Cantón Colta para promover el desarrollo local. - Jara Montoya, Alejandra Geovanna (2016)
: Ecuador is a country with great tourism potential, with the greatest diversity on the planet, within there are different indigenous nationalities, who are noted for their varied culture and diversity, among these are those belonging to the highlands, which has a rich cultural. It certainly is a mega-diverse country, because thanks to their great contrast in its small territory combines four natural regions offering a wealth of soils, climate, mountains, deserts, beaches, islands and jungle. Colta has a great cultural tourism potential, but one of the problems lies in the unawareness of it is deficit tourism services that are affecting today's, social problems has been established in Colta, migration due to lack of jobs, the fading traditions, customs of the communities and the inclusion of modern lifestyles that affect to the culture of the Colta. Strategic Plan is a tool of local development that has not been deployed. Strategic plans have become the boom of new strategies to improvement and promote tourism in different countries, it is important to mention that Mexico has achieved development through cultural tourism. This is why it is necessary to carry out the proposal stated in this research is the strategic plan of offer tourism services in Colta so that in this way generate local development. In this work strategic plan to offer tourism services as a proposal of this research whose content is divided into eight chapters distributed as follows: Introduction, the general frame of the tourism situation and short summary of the investigation. In Chapter I, it is part of the theoretical framework, where the background of research, basic concepts, basic terms, assumptions and the variables argues. In Chapter II, describes the methodological system, it provides the tools and instruments to collect essential information for investigative work, allowing use of proper form the necessary technical development work. In Chapter III make the results of the investigation, based on the technique, interpretation, analysis and validation of the diagnosis results situation where specific data on social organization, ethnic composition, tourist facilities, tourist infrastructure; etc.; is also the analysis of the survey of tourism, DAFO analysis and matrix CPES these result in the final proposal. In Chapter IV, the same discussion will help determine the type of the situation of tourism services of the Colta. In Chapter V, there are conclusions and recommendations by this research. In Chapter VI, the detailed proposal with the introduction, objectives, the scientific and technological foundation, the description of the proposal, organizational design and monitoring and evaluation. In Chapter VII, is detailed bibliography and linkongraphy that were used in the investigation. Chapter VIII, annexes, is the strategic plan, the survey, BMP tab, interviews and photographs of the research process.